Business System Development Strategies In MSMEs In Order To Sustanable Increase - Suranto Suranto; Taufan Rizki Afianto; Etika Muslimah; Indah Pratiwi (Jurnal Info Sains : Informatika dan Sains, 2023)
MSMEs Rizkya Gaya Busana (MSMEs RGB), one of the MSMEs in Surakarta, is experiencing problems related to decreasing sales turnover, decreasing the number of consumers, and decreasing the amount of production. This research aims to identify internal and external factors encountered by MSMEs so as to produce alternative benefits for the right sales strategy so that they can rise and move on to compete. Data collection methods are with interviews, questionnaires, observation and documentation. Development of business system strategies is through the SWOT analysis method, for identification and strategic business development plans. Based on the results of data processing and SWOT analysis, it is known that RGB's business conditions are in quadrant one position, so the right strategy is to support growth oriented strategy. Development is sought and advised to focus on maximizing the strengths and opportunities possessed by MSMEs, through: (1) progressive development of e-commerce websites, (2) establishing partnerships in creating sales collaborations and reaching a different customer base segment, (3), identifying unmet market needs, and; (4) utilizing advertising and promotion features on social media to increase brand visibility and branding.